The association between polyphenol consumption and stroke risk factors in Saudi Arabia - Alsharif, Sarah N. (Frontiers in Nutrition, 2026)
IntroductionEating foods rich in polyphenols has been shown in numerous trials to lower the incidence of stroke. The present study aimed to evaluate the relationship between stroke risk variables and the consumption of polyphenols.MethodsAn online questionnaire was used to conduct a cross-sectional study involving 293 healthy persons aged at least 18 years in Saudi Arabia. Information was gathered on the demographics, health, use of supplements or drugs, smoking, anthropometric measures, physical activity, and dietary intake of six food products high in polyphenols.ResultsThe mean age of the participants was 34.82 ± 14.06 years, 72.7% were women, 51.5% were married, and 63.1% had a university education. Of them, 23.5% were obese and 62.8% were performing physical activity. Almost all participants had ≥3 modifiable stroke risk factors. Coffee was the most consumed polyphenol product (91.3%), followed by dates (88.7%) and apples (88.4%). Foods high in polyphenols were consumed anywhere from four to five times per day to less than once per month. The most commonly consumed polyphenol-rich foods were found in black tea, coffee, and apples. Except for milk chocolate, older participants consumed significantly greater amounts of polyphenol-containing food than younger ones. A higher intake of apples or dark chocolate was associated with a lower probability of having a stroke. Additionally, the risk of stroke is decreased by consuming more dark chocolate, cocoa powder, coffee, apples, black tea, and green tea.DiscussionOverall, adult Saudi Arabians who consumed more of a specific food high in polyphenols had a lower incidence of stroke. Additional long-term cohort studies is recommended to obtain more precise dietary data and to take into account randomized controlled trials to prove causation.